Homogeneous application of imaging criteria in a multicenter trial supported by investigator training: A report from the WAKE-UP study. Issue 104 (July 2018) - Galinovic, Ivana; Dicken, Volker; Heitz, Johannes; Klein, Jan; Puig, Josep; Guibernau, Jorge; Kemmling, Andre; Gellissen, Susanne; Villringer, Kersten; Neeb, Lars; Gregori, Johannes; Weiler, Florian; et al.
Abstract: Background and Purpose: WAKE-UP is a randomized, placebo-controlled trial of thrombolysis in stroke with unknown time of symptom onset using magnetic resonance imaging criteria to determine patients' eligibility. As it is a multicenter trial, homogeneous interpretation of criteria is an important contributor to the trial's success. We describe the investigator image training as well as results of the quality control done by the central image reading board (CIRB). Methods: Investigators at local centers were given an imaging manual and passed a software-based image training prior to being allowed to judge images in the trial. Throughout the trial, the CIRB gave feedback to recruiting centers in cases of disagreement regarding a patient's randomization. We evaluated the investigators performance in the image training and analyzed results of this quality control from the first 1069 screened patients. Additionally, we obtained feedback from investigators regarding their experiences with the trial. Results: Four-hundred-and-sixty physicians from eight European countries took part in the image training, of whom 436 (95%) successfully completed it. In the trial, agreement rates between the local investigators and members of the CIRB were high for the presence of an acute ischemic lesion (94%, κ = 0.87) as well as for the judgment of infarct extent (93%, κ = 0.87). Agreement for the criterion of DWI-FLAIR mismatch was 74%, κ = 0.60. The majority of investigators reported that the DWI-FLAIR mismatch was the hardest imaging criterion to evaluate. Ninety-one percent of investigators who responded to our survey stated that the image training specifically increased their confidence when assessing the DWI-FLAIR mismatch. Conclusions: Despite its multicenter design, the WAKE-UP study has demonstrated a high level of homogeneity amongst raters in interpreting the various imaging criteria for patient randomization, including the novel criterion of DWI-FLAIR mismatch. Systematic image training increased the confidence of investigators in applying imaging criteria.